2020
DOI: 10.1177/0269215520984321
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Cumulated Ambulation Score French translation

Abstract: Objective: To examine measurement properties (inter-rater reliability, agreement, validity, and responsiveness) of the Cumulated Ambulation Score French translation in patients with hip fracture. Design: Methodological study. Setting: A 20-bed orthopedic unit and 20-bed geriatric unit. Subjects: About 140 consecutive patients with a mean (SD) age of 83 (12) years. Interventions: The English version of the Cumulated Ambulation Score used to evaluate basic mobility was translated into French following internatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
1
5
1
Order By: Relevance
“…The CAS-JP effect size in the present study was large at all time points and was even higher than that previously reported by Hulsbaek et al 19) They also reported a large CAS effect size (1.04) when used from POD1 to the time of discharge (mean length of stay: 8 days) in a Danish setting. The ef- fect sizes on POD14 and discharge in the current study were higher than those reported in previous studies, 19,28) which may be explained by greater mobility recovery with the longer follow-up period in the current study. The MCID of the CAS-JP in this study ranged from 0.51 to 0.69 CAS points, which is similar to the MCID of 0.8 reported in a previous study.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…The CAS-JP effect size in the present study was large at all time points and was even higher than that previously reported by Hulsbaek et al 19) They also reported a large CAS effect size (1.04) when used from POD1 to the time of discharge (mean length of stay: 8 days) in a Danish setting. The ef- fect sizes on POD14 and discharge in the current study were higher than those reported in previous studies, 19,28) which may be explained by greater mobility recovery with the longer follow-up period in the current study. The MCID of the CAS-JP in this study ranged from 0.51 to 0.69 CAS points, which is similar to the MCID of 0.8 reported in a previous study.…”
Section: Discussioncontrasting
confidence: 85%
“…Previous studies have reported correlation coefficients be- tween CAS and BI of 0.33-0.60 19,24,27) and between CAS and other mobility outcomes of 0.56-0.90 19,24,28,30) ; the CAS-JP in this study showed the same or higher associations. However, there was a weaker correlation between CAS-JP and BI on POD1, a finding that corresponds to those of a previous study.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…14 At present, the CAS manual and score sheet is freely available in 18 languages. The CAS has established reliability 13,[15][16][17][18][19] and proven valid in reflecting the early post-hip fracture mobility outcome, [20][21][22] and as a strong predictor of outcome for patients after hip fracture. 14,23 The dependent variable was a binary indicator of 30-day postoperative mortality as recorded by the multidisciplinary Danish national hip fracture register.…”
Section: Discussionmentioning
confidence: 99%
“…Pain while resting, standing, and walking was assessed using an 11-point numeric rating scale (0 = no pain to 10 = maximal pain) by nurses and physiotherapists who were blinded with respect to the intervention. Functional capacity and rehabilitation were assessed daily using the Cumulated Ambulation Score (CAS) 18,19 by physiotherapists. This includes 3 activities-getting in and out of bed, sitting down in and standing up from a chair, and walking ability-rated on a 3-point scale (0 = "not able to" to 2 = "independent").…”
Section: Study Outcomesmentioning
confidence: 99%